Anatomical Differences Between Intact and Ruptured Large Abdominal Aortic Aneurysms. (February 2020) - Spanos, Konstantinos; Nana, Petroula; Kouvelos, George; Mpatzalexis, Konstantinos; Matsagkas, Miltiadis; Giannoukas, Athanasios D.
Purpose: To compare different anatomical characteristics between intact and ruptured large abdominal aortic aneurysms (rAAA >80 mm) with the goal of refining the process of estimating rupture risk.Materials and Methods: A retrospective study involving 62 male patients with large (>80 mm) aneurysms matched for age and smoking produced a 31-patient elective group with a mean maximum aneurysm diameter of 92±9.7 mm and a 31-patient rAAA group (mean maximum aneurysm diameter 95.7±12 mm). Preoperative computed tomography angiography scans were analyzed with a dedicated workstation, and anatomical characteristics of the aortic neck, iliac arteries, and aneurysm were compared in multivariable regression analyses; the outcomes are given as the odds ratio (OR) with 95% confidence interval (CI). The prognostic utility of several characteristics as predictors of rupture occurrence was examined with receiver operating characteristic (ROC) curves.Results: Anatomical characteristics differing significantly between elective and ruptured aneurysms were the infrarenal aortic neck diameters at 5 mm, 10 mm and 15 mm; the neck length and calcification; the common iliac artery (CIA) lengths; the iliac artery indexes; the left CIA and external iliac artery diameters; and the total and true lumen aneurysm volumes. Intraluminal thrombus (ILT) volume did not differ (p=0.76), although its distribution in elective vs ruptured cases did [absent: 0% vs 19%, respectively (p=0.025); circumferential: 61% vs 35%, respectively (p=0.04)]. Total aneurysm volume was higher in rAAA (442±140 mL) vs intact AAA (331±143 mL, p=0.014), while the ILT/total aneurysm volume rate was lower in rAAA (55%) vs intact AAA (70%, p=0.02). Multivariate analysis determined that a shorter left CIA (OR 1.07, 95% CI 1.01 to 1.1, p=0.016) and a smaller total aneurysm volume (OR 1.007, CI. 1.001 to 1.014, p=0.016) were associated with intact AAA. After a ROC curve analysis, left CIA length <50 mm demonstrated a lower incidence of rupture (sensitivity 60% and specificity 78%), while total aneurysm volume <380 mL had 60% sensitivity and specificity.Conclusion: Large rAAAs seem to have different anatomical characteristics than similarly sized intact AAAs. Large intact AAAs have lower total aneurysm volumes and shorter left CIAs, with higher ILT/aneurysm volume rates.